Addition of various sources of natural beta carotene to increase the color brightness of guppy (Poecilia reticulata) - Khaira, Fadhila; Wahyudin, Yudi; Farastuti, Eko Rini (JURNAL MINA SAINS, 2024)
The challenge for ornamental fish farmers is to maintain the brightness of the color so that it remains charming and beautiful in the fish being cultivated. This study aims to determine the level of Colour brightness of guppies (Poecilia reticulata) by supplementation with different sources of natural beta-carotene. The research was conducted from May to June 2023. This study used a fully randomized design with four treatments and three replicates. Pellets were given as control, with treatments of pumpkin flour, carrot flour, and yellow sweet potato flour. Measurement of fish brightness level using M-TCF (Modifed-Toca Color Finder). The test fish were guppies from Fajar Aquatiq measuring 2.1-2.9 cm. The guppies were stocked at a density of 6 fish/aquarium and tested for 28 days. The observation of color quality showed that the P3 treatment with carrot flour of 10g/100g feed showed the highest color improvement of 26.57 ± 0.32. The best value of absolute weight growth in the treatment of three carrot flour was 0.12 ± 0.05g, and the lowest was in P1 with an average of 0.09 ± 0.03g. The best value of absolute length growth in P3 treatment was 0.80 ± 0.10 cm, while the lowest value was in P1 and P4 with 0.77 ± 0.06 cm. The highest survival value in the P2, P3, and P4 treatments was 100.00 ± 0.00%, while the lowest was in P1 94.33 ± 9.81%.